2022
DOI: 10.3390/f13091369
|View full text |Cite
|
Sign up to set email alerts
|

Management of Recreational Forests in the Romanian Carpathians

Abstract: Research Highlights: Forests, due to their aesthetic properties, have huge recreational potential, but their management must take into account the requirements of all parties interested in these services. Background and Objectives: We sought to determine the main indicators that characterize the structural diversity of a recreational mountain forest, with relevance for the management of these forests, given that they fulfill multiple functions. Materials and Methods: The structure of 446 stands was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…As can be seen from the results of this study, visitors mainly preferred unmanaged stands (i.e., UMS and OGD) or moderately treated stand (i.e., MMS) for the recreational activities, in comparison to the previously managed stands (i.e., MGS and MSW). Similar results are described in previous research that found more natural areas are highly appreciated by people (Gundersen and Vistad 2016;Tudoran et al 2022). People mostly believe that old trees, species composition, multi-layer canopy tiers, straightforward forest paths, and fewer signs following forestry operations should all contribute to the forest's natural appearance (Gundersen and Frivold 2008;Wang et al 2022).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As can be seen from the results of this study, visitors mainly preferred unmanaged stands (i.e., UMS and OGD) or moderately treated stand (i.e., MMS) for the recreational activities, in comparison to the previously managed stands (i.e., MGS and MSW). Similar results are described in previous research that found more natural areas are highly appreciated by people (Gundersen and Vistad 2016;Tudoran et al 2022). People mostly believe that old trees, species composition, multi-layer canopy tiers, straightforward forest paths, and fewer signs following forestry operations should all contribute to the forest's natural appearance (Gundersen and Frivold 2008;Wang et al 2022).…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, stands with greater amount of dead trees can also increase recreational values of forests, and highly preferred by public (Topaçoğlu et al 2017;Kara and Lhotka 2020;Sacher et al 2022). The understanding of the linkage between silvicultural prescriptions and recreation demands of society would help forest managers to develop better and more comprehensive management strategies which aim to enhance recreational values of stands while producing timber (Maier and Winkel 2017;Tudoran et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the synergies and trade-offs of ecosystem services could provide a baseline for comparing alternative future scenarios and insights into potential policy and management outcomes (Bryan, 2013;Mouchet et al, 2014). Even with ecosystem service like Recreation, which is yet a poorly developed economic sector on typical forest land in all studied areas, an expected increased influence on future forest management (Tudoran et al, 2022) will need to be considered in any implementation. Others more established, like wood production are balanced with recreation over time, but it is essential to develop site-specific management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, complexity emphasizes the need for a system and arrangement to demonstrate highly ordered complexity for high aesthetic quality [8,9]. Visual forest complexity or variety positively affects forest value and public preferences because of the diversity of visual connections between forest elements [50,58]. Complexity has been found to be significant in forest guidelines, forest management, and forest aesthetics preferences [51,55,56,[59][60][61].…”
Section: • Complexitymentioning
confidence: 99%